SERS and electrochemical impedance spectroscopy immunoassay for carcinoembryonic antigen - Guerrero, Yuselis (2021)
This work describes an innovative dual detection approach, combining electrochemical and surface-enhanced Raman scattering (SERS) sequential readings, on the same sensing surface. This was achieved by establishing (i) an antibody binding stage on a suitably modified screen-printed electrode (Au-SPE), to produce an electrochemical signalling system, followed by (ii) a second antibody binding stage, on the same sensing surface, comprising gold nanostars (AuNS) with a suitable Raman reporter, and acting as a second signalling system (SERS). This simple principle is applied herein to carcinoembryonic antigen (CEA) detection. The first layer of antibodies was assembled on the Au-SPE previously modified with a cysteamine layer. Binding to CEA was allowed for 30 minutes. Electrochemical impedance spectroscopy (EIS) readings followed the several stages of Au-SPE modification and generated analytical data. After, the AuNS were modified with 4-aminothiophenol (4-ATP)/Ab-CEA, and incubated on the same sensing surface, to provide SERS data. The analytical features were checked for both EIS and SERS. In EIS, the sensor showed linear response range from 0.25 to 250 ng/mL, with a linear correlation coefficient of 0.991, evaluated in serum. It also demonstrated good selectivity against creatinine and glucose. Using the SERS as signalling system, the spectra confirmed differentiated signals from the background within 0.025 ng/mL to 250 ng/mL of CEA. As expected, the Raman signal of the reporter increased with increasing CEA concentrations, and contributed to confirm the accuracy of the analytical data. Overall, this approach is simple, and may be adaptable to new multiplexing devices, also being adaptable to mass production.